«ÓNIM TAYARLAW TEXNOLOGIYASÍ» PÁNIN ARALÍQTAN OQÍTÍWDA ZAMANAGÓY BILIM BERIW QURALLARÍNÍŃ ORNÍ - Utambetov, B.; Qalmuratova, X. (SCIENCE and SOCIETY, 2025)
The article provides information on the use of software and technical means at their level, their high quality and wide capabilities to create audio, video, graphic and other elements of media education, create traditional text materials, independently create media materials, use them as a student, and ensure the effective use of media education tools in teaching the subject of product manufacturing technology.